TINGKAT PENGARUH KEPUASAN KERJA DAN KOMPENSASI TERHADAP TURNOVER INTENTION KARYAWAN CV. GEOPUBLISH INDONESIA KOTA MAKASSAR - Rais Rais; Rr Retno Wulansari Kus; Suwardy Suwardy; Muhtar Muhtar; Vivian Nova (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2026)
The purpose of this study was to analyze the influence of Job Satisfaction and Compensation on Turnover Intention among employees at CV. Geopublish Indonesia in Makassar City and to analyze the simultaneous influence of Job Satisfaction and Compensation on Turnover. This study was conducted on 64 employees of CV. Geopublish Indonesia in Makassar City. Descriptive data analysis was used to explain the characteristics of the respondents and describe the research variables. The quantitative data were then analyzed using multiple regression analysis using the Statistical Package for Social Science (SPSS) to obtain information regarding the influence of Job Satisfaction and Compensation on Turnover, both simultaneously and partially. The results of this study indicate that simultaneously or as a whole, Job Satisfaction and Compensation variables have a significant positive effect on Turnover, and partially, Job Satisfaction has an insignificant effect on Turnover at CV. Geopublish Indonesia in Makassar City. The results also indicate that to reduce turnover, it is necessary to address fair and transparent compensation provided to employees.